THE HISTORICAL AND CULTURAL ORIGINS OF YUNNAN TEA - XIAO, YING; BAO, ZHONGHUA; LIU, CHUXIAO (Chinese Language and Culture Journal, 2020)
Tea comes from China. Yunnan is the hometown of tea. Based on the historical documents and field investigation, this paper points out that the nations represented by Bulang and Jinuo ethnic groups and the areas where their ancestors lived are the origin of tea sources in the world. Up to now, in all 26 ethnic groups in Yunnan, there are worship of tea ancestors and exhibition of tea culture. The article also focuses on the ancient tea mountain in Pu'er City, Yunnan Province, and introduces the historical evolution and distribution of tea resources. The orderly development and utilization of tea resources is of great significance to the promotion of local economic and social development and national harmony.